Immunomodulatory Potential of Curcuma longa Extract as Adjuvant Therapy for Peritonitis: A Systematic Review of Inflammatory Biomarkers IL-6 and Myeloperoxidase - Ishak Andreas Soritua Lumban Gaol; Endang Mahati; Erik Prabowo (Green Publisher Indonesia, 2026)
Peritonitis is a severe inflammatory condition of the peritoneum associated with high morbidity and mortality, often progressing to sepsis due to excessive inflammatory responses. Pro-inflammatory cytokines such as interleukin-6 (IL-6) and neutrophil-derived enzymes like myeloperoxidase (MPO) play critical roles in disease progression and tissue damage. Current treatments primarily focus on infection control; however, adjunctive therapies targeting inflammation remain limited. This study aims to evaluate the potential of Curcuma longa extract as an adjuvant therapy in modulating IL-6 levels and MPO activity in peritonitis. This research employed a systematic review design following PRISMA 2020 guidelines. Literature was collected from Scopus, PubMed, Google Scholar, and ScienceDirect using predefined inclusion and exclusion criteria. A total of four eligible experimental studies (in vivo and in vitro) were analyzed. The findings demonstrate that Curcuma longa extract, particularly curcumin, significantly reduces IL-6 expression and modulates MPO activity, indicating decreased inflammatory response and neutrophil infiltration. These effects are associated with the inhibition of key inflammatory pathways such as NF-κB and MAPK.In conclusion, Curcuma longa shows promising potential as an adjunctive therapy for peritonitis by attenuating inflammatory biomarkers. However, further standardized studies and clinical trials are required to confirm its efficacy and optimal therapeutic dosage.